Parent‐conducted rapid assessment of attention types for the treatment of attention‐maintained problem behavior. (22nd January 2021) - Livingston, Cynthia; Adams, Molly B.; Strohmeier, Craig W.
Abstract: When praise is not a reinforcer for alternative behavior in the treatment of attention‐maintained problem behavior, further pretreatment assessments are warranted to develop an effective treatment. The current study reports a replication of the pretreatment rapid assessment of attention types (RAAT) procedures, implemented by the parents of a 19‐year‐old female with attention‐maintained problem behavior. After administering staff and parent‐conducted RAATs, a parent‐implemented treatment, (a) produced clinically significant decreases in problem behavior, and (b) confirmed that the RAAT identified an attention‐type that served as a reinforcer for appropriate alternative behavior. This study extends the findings of Strohmeier et al. by reporting results of a parent‐conducted RAAT and treatment evaluation. The findings highlight the practical importance of pretreatment assessment of attention‐types, with emphasis on caregiver involvement, to develop effective treatments for attention‐maintained problem behavior.